Preparation of Three-Dimensional Vascularized MSC Cell Sheet Constructs for Tissue Regeneration. (8th July 2014) - Ren, Liling; Ma, Dongyang; Liu, Bin; Li, Jinda; Chen, Jia; Yang, Dan; Gao, Peng
Abstract : Engineering three-dimensional (3D) vascularized constructs remains a challenge due to the inability to form rich microvessel networks. In this study we engineered a prevascularized 3D cell sheet construct for tissue regeneration using human bone marrow-derived mesenchymal stem cells (hMSCs) and human umbilical vein endothelial cells as cell sources. hMSCs were cultured to form a thick cell sheet, and human umbilical vein endothelial cells (HUVECs) were then seeded on the hMSCs sheet to form networks. The single prevascularized HUVEC/hMSC cell sheet was folded to form a 3D construct by a modified cell sheet engineering technique. In vitro results indicated that the hMSCs cell sheet promoted the HUVECs cell migration to form networks in horizontal and vertical directions. In vivo results showed that many blood vessels grew into the 3D HUVEC/hMSC cell sheet constructs after implanted in the subcutaneous pocket of immunodeficient mice. The density of blood vessels in the prevascularized constructs was higher than that in the nonprevascularized constructs. Immunohistochemistry staining further showed that in vitro preformed human capillaries in the prevascularized constructs anastomosed with the host vasculature to form functional blood vessels. These results suggest the promising potential of this 3D prevascularized construct using hMSCs cell sheet as a platform for wide applications in engineering vascularized tissues.